The «tortuous path» of literacy in post-unitary Sardinia. The case of primary education in the province of Cagliari through the quantitative analysis of the statistics offered by the R. School Inspector Giovanni Scrivante (1861-1864) - Garau, Manuela (Rivista di Storia dell’Educazione, 2022)
The essay reconstructs the state of primary education in the province of Cagliari, including, the districts of Oristano, Iglesias, Lanusei and the capital, in the aftermath of the Unification of Italy. The analysis starts from the years 1861-1864, through a comparison with primary education statistics in the school year 1853-1854, when the Island was still part of the Regnum Sardiniae, exactly one lustre before the approval of the Casati Law. This comparison, in the largest and most populous province of Sardinia (13,415.22 sq. km. and 372,097 inhabitants at the 1861 census), is made through the study, re-presentation and re-elaboration of the statistical summaries presented and published by the Timon Typography of Cagliari in 1864 at the behest of the Royal School Inspector ff. di Provveditore, Giovanni Scrivante, who made use not only of his work for the years 1863 and 1864, but also of the work on the initiation and dissemination of elementary schools, carried out by his predecessor, Cav. Alberto De Gioannis, in the two-year period 1861-1862. The article addresses the status and diffusion of public and private elementary schools for both boys and girls, as well as mixed schools and evening and holiday schools for adults. The essay reconstructs the state of primary education in the province of Cagliari, in the aftermath of the Unification of Italy. The analysis starts from the years 1861-1864, through a comparison with primary education statistics in the school year 1853-1854. This comparison, in the largest and most populous province of Sardinia, is made through the study, re-presentation and re-elaboration of the statistical summaries presented and published in 1864 by the School Inspector Giovanni Scrivante.